On the grain size dependence of shock responses in nanocrystalline sic ceramics at high strain rates. (November 2020) - Li, Wanghui; Hahn, Eric N.; Yao, Xiaohu; Germann, Timothy C.; Feng, Biao; Zhang, Xiaoqing
Abstract: Shock induced plasticity, structural phase transitions, as well as dynamic failure in nanocrystalline SiC ceramics, with grain sizes varying from ~2 to ~32 nm, are investigated systematically using large scale molecular dynamics simulations. Shock particle velocities are varied from 1 to 5 km/s in order to study elastic and plastic behavior. Multiple non-monotonic grain-size dependent mechanical properties of nanocrystalline SiC are elucidated. Deformation twinning identified at U p  = 2 km/s is reduced with decreasing grain size with a breakdown between dG  = 6 to 10 nm. Statistics from grain size effects on the phase transformation from Zinc-Blend to Rock-Salt structure at different particle velocities are obtained. The characteristics of failure shift from classical spall to micro-spall as U p is increased from 1 to 5 km/s. Spall strengths are evaluated by an indirect free-surface method, akin to experimental measurements, and a direct method evaluating the atomic stress tensor at the point of spallation. Differences between the two methods at high strain rates are discussed in detail. The direct method provides a measure of ultimate spall strength, while the indirect method shows pronounced agreement with the nucleation stress. An unexpected grain size dependence of the tensile strengths is also identified, which is similar to a theoretically predicted trend in nanoscale systems. Our results provide new support to the grain size dependence of mechanical properties of nanocrystalline system at high strain rates, which could benefit the design of nanocrystalline ceramics. Graphical abstract: Graphical abstract Image, graphical abstract